Purchase Intension of Second Hand Product that Unconsciously Move toward Voluntary Simplicity: A Netnographic Observation from Sweden and Bangladesh - Rahman, Mohammad Ataur (American Journal of Trade and Policy, 2018)
Voluntary simplicity is one of the desired lifestyle that modern consumers wants to live. But, becoming voluntary simplifiers is not an easy task. There are several ways of becoming voluntary simplifiers and one of the common way is buying second hand products. Purchase intension of second hand consumers is maintained by consumers’ conscious and unconscious mind. Unconscious mind mainly decide whether a consumer will go for the second hand product or not? In this study, consumers of Sweden and Bangladesh has been focused to check their purchase intension of second hand product that unconsciously move them to become voluntary simplifiers. From the Netnographic observation, it has been found that, Bangladeshi consumers are more voluntary simplifiers than that of Swedish consumers because of their unconscious mind.
Keywords: Purchase Intension; Second Hand Product; Netnographic Observation; Sweden; Bangladesh